A Comparison of Radial and Horizontal Macular Optical Coherence Tomography on Detection of Macular Pathology: A Prospective Study at an Academic Institution. (November 2021) - Blegen, Halward M.J.; Hobbs, Samuel D.; Taylor, Reggie; Plaster, Andrew L.; Drayna, Paul M.
Purpose: Optical coherence tomography (OCT) is useful in diagnosing and monitoring retinal pathology such as age-related macular degeneration, diabetic macular edema (DME), central serous chorioretinopathy, and epiretinal membrane, among others. This study compared the ability of horizontal (H) 25-, 13-, and 7-cut macular OCT vs 24-, 12-, and 6-cut radial (R) macular OCT in identifying various macular pathology. Methods: This was a prospective study of 161 established patients evaluated at Wilford Hall Eye Center Retina Clinic between September and October of 2019. Pathology included age-related macular degeneration, central serous chorioretinopathy, DME, and epiretinal membrane, among others. Patients obtained 25-, 13-, and 7-cut H raster OCT as well as 24-, 12-, and 6-cut R OCT. Primary outcomes were sensitivity in detecting macular fluid and each macular abnormality. Results: The 24-cut radial (R24) OCT equally or out-performed the H25 (horizontal 25-cut OCT) in detecting macular fluid across all pathological groups. Generally, a higher number of cuts correlated with better detection of fluid. In detecting any macular abnormalities, H25, R24, and R12 had 100% sensitivity. R6 OCT had near 100% sensitivity across all groups, except for DME (95%). Overall, R OCT had better sensitivity (0.960) than H OCT (0.907) in detecting macular pathology. Conclusions: R outperformed H macular OCT in detecting fluid and other abnormalities. Clinically, both scanning patterns can be used by ophthalmologists in diagnosis and management of commonly encountered macular diseases. Technicians may be able to use a variety of these scans to screen for pathology prior to physician evaluation.